Taurog’s 1931 adaptation of Mark Twain’s The Adventures of Huckleberry Finn: An Existential Reality of America in the 1860’s - Asghar Moulavinafchi; Laleh Atashi; Alireza Anushiravani (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Adaptation studies gained a renewed focus on the understanding of the mutations contained in the area of film adaptation namely by drawing on theorists like Linda Hutcheon and Robert Stam. This being the case, studying the film adaptation is to work as a platform to detect the social, political and cultural changes of the history. Twain’s The Adventures of Huckleberry Finn as a nationally definitive work for the American literature has been persistently adapted to films since the advent of cinema. Mostly these adaptations occur at specific historical times in American history like Taurog’s adaptation of The Adventures of Huckleberry Finn (1931) that studies the existential reality of the novel during the 1860s. And as adaptation studies, in this perspective, expand the horizon for cultural materialists who investigate the historicity of the text, the type of thinking that is promoted in this study is how the film adaptation ideologically has challenged the core of this nationally definitive text of American literature to further probe into the social and historical issues of the time of adaptations.